An integrated cytokine and kynurenine network as the basis of neuroimmune communication - Stone, Trevor W.; Clanchy, Felix I. L.; Huang, Yi-Shu; Chiang, Nien-Yi; Darlington, L. Gail; Williams, Richard O. (Frontiers in Neuroscience, 2022)
Two of the molecular families closely associated with mediating communication between the brain and immune system are cytokines and the kynurenine metabolites of tryptophan. Both groups regulate neuron and glial activity in the CNS and leucocyte function in the immune system, although neither group alone completely explains neuroimmune function, disease occurrence or severity. This essay suggests that the two families perform complementary functions generating an integrated network. The kynurenine pathway determines overall neuronal excitability and plasticity by modulating glutamate receptors and GPR35 activity across the CNS, and regulates general features of immune cell status, surveillance and tolerance which often involves the Aryl Hydrocarbon Receptor (AHR). Equally, cytokines and chemokines define and regulate specific populations of neurons, glia or immune system leucocytes, generating more specific responses within restricted CNS regions or leucocyte populations. In addition, as there is a much larger variety of these compounds, their homing properties enable the superimposition of dynamic variations of cell activity upon local, spatially limited, cell populations. This would in principle allow the targeting of potential treatments to restricted regions of the CNS. The proposed synergistic interface of ‘tonic’ kynurenine pathway affecting baseline activity and the superimposed ‘phasic’ cytokine system would constitute an integrated network explaining some features of neuroimmune communication. The concept would broaden the scope for the development of new treatments for disorders involving both the CNS and immune systems, with safer and more effective agents targeted to specific CNS regions.